The Legal Protection Of Workers' Rights Fulfillment Of The Homeworker In The Industrial Relations Court Semarang - Siti Putri Indah Meilani (Jurnal Daulat Hukum, 2019)
The study on “The Legal Protection of Workers' Rights Fulfillment of The Homeworker In the Industrial Relations Court Semarang" aims to: 1) analyze the legal protection of the fulfillment of the rights of homeworkers in the Industrial Relations Court Semarang. 2) analyze the decision of the Industrial Relations Court of Semarang on the fulfillment of the rights of homeworkers. Methods of research in this thesis using sociological juridical approach to the specification of descriptive analysis is the method of collecting data to obtain data that will be used as a thesis through interviews with homeworkers in the Industrial Relations Court Semarang, or by observation in the form of observations systematically involved in obtaining the data. Afterwards will be analyzed data obtained from various sources qualitatively. The results showed that: 1) homeworkers have not received the fulfillment of the rights as workers. 2) based on the right trial Industrial Relations Decision No. 26 / Pdt.Sus-PHI / 2018 / PN.Smg states that homeworkers have the same status as formal workers who work in the company so that they are entitled to the fulfillment of workers' rights as stipulated in the Act No. 13 of 2003 on Labor. Keywords: Legal Protection of Workers; The Industrial Relations Court.